Dynamic Janus metasurfaces in the visible spectral region - Yu, Ping; Li, Jianxiong; Zhang, Shuang; Jin, Zhongwei; Schütz, Gisela; Qiu, Cheng-Wei; Hirscher, Michael; Liu, Na (Nano letters, 2018)
Janus monolayers have long been captivated as a popular notion for breaking in-plane and out-of-plane structural symmetry. Originated from chemistry and materials science, the concept of Janus functions have been recently extended to ultrathin metasurfaces by arranging meta-atoms asymmetrically with respect to the propagation or polarization direction of the incident light. However, such metasurfaces are intrinsically static and the information they carry can be straightforwardly decrypted by scanning the incident light directions and polarization states once the devices are fabricated. In this Letter, we present a dynamic Janus metasurface scheme in the visible spectral region. In each super unit cell, three plasmonic pixels are categorized into two sets. One set contains a magnesium nanorod and a gold nanorod that are orthogonally oriented with respect to each other, working as counter pixels. The other set only contains a magnesium nanorod. The effective pixels on the Janus metasurface can be reversibly regulated by hydrogenation/dehydrogenation of the magnesium nanorods. Such dynamic controllability at visible frequencies allows for flat optical elements with novel functionalities including beam steering, bifocal lensing, holographic encryption, and dual optical function switching.
Gesehen am 05.03.2020